Characterization of Polyphenols from Various Cocoa (Theobroma cacao L.) Clones During Fermentation - Muhammad Isa Dwijatmoko; Budi Nurtama; Nancy Dewi Yuliana; Misnawi Misnawi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Cocoa bean is a rich source of polyphenols, which are the largest group secondary metabolite with natural antioxidant property. Polyphenols from cocoabeans was reported to possess health benefits. Fermentation, one step in cocoa processing is needed to improve the quality of cocoa in which the concentration of cocoa bean polyphenols might decrease significantly through oxidation and exudation. Cocoa polyphenols content among different cocoa clones mightalso vary. The aims of this study were to determine total polyphenols, total flavanoid, epicatechin, and catechin content in several cocoa clones, those wereSulawesi 1, Sulawesi 2, ICCRI 03, and KW 617. Until now, characterization of polyphenols from those clones has not been reported. The effect of five daysfermentation to those parameters was also studied. The results of the study showed that fermentation and type of clones significantly affected total of polyphenols, total of flavanoids, epicatechin, and catechin content of the cocoa, there is also an interaction between fermentation and type of clones. Unfermented of Sulawesi 1 had the highest total polyphenols of 96.94±5.83 mg/g, total flavanoids of 90.92±1.89 mg/g, epicatechin of 52.50±0.46 mg/g, and catechin of 1.99±0.02 mg/g content compared to other clones. Among five days fermented cocoa beans, Sulawesi 2 showed the highest total polyphenols and total flavanoids content, while ICCRI 03 had the highest epicatechin and catechin content than other clones. Thus, in can be concluded that although fermentation is required to improve the flavor quality of cocoa, it significantly reduced the content of bioactive compounds. This effect varied amongdifferent cocoa clones.